Performance Analysis of 22 MWp Solar Power Plant: (Case Study at PT Riau Andalan Pulp and Paper) - Arief Fachrozi; Siti Anisah; Rahmaniar Rahmaniar (Publikasi Indonesia, 2025)
The global transition towards sustainable energy sources is increasingly urgent as fossil fuel reserves decline and environmental concerns rise. Indonesia, with its significant potential for renewable energy, particularly solar power, has made substantial progress in integrating cleaner energy sources. However, the current utilization rate remains low, highlighting the need for effective strategies to harness this potential. This research examines the performance of the 22 MWp solar power plant at PT Riau Andalan Pulp and Paper (APRIL Group) as a case study to explore the role of solar energy in industrial applications. The study aims to analyze the efficiency, reliability, and overall contribution of the solar power plant to the company’s energy demands while identifying operational challenges. Using historical data from the solar PV monitoring system, the research evaluates monthly energy production, performance trends, and CO2 emissions reductions over three months (April–June 2024). Key findings indicate that solar energy significantly contributes to reducing carbon footprints and improving energy sustainability. This research provides valuable insights into the optimization of solar power plants and underscores their critical role in advancing Indonesia's renewable energy agenda.